Algoritma Fuzzy Analytic Hierarchy Prosess (AHP) Guna Menentukan Re-Order Barang Persediaan di Departement Store Laris Kartasura Sukoharjo - Taufik Nurhidayat (Politeknosains, 2020)
At the beginning, stock management in retails was applied to guarantee the stock always available and ready to sell to the consuments. But at now, stock management to be a critical matter in retails. Together with strict trade competition, the opportunity of stock management applied is changed into planning, doing, and controlling stock need in business. So, the need of operational business can compiled at time and the other side the cost can be pressured.By using stock method that existence now (ABC method) is not giving maximum service yet because there are dependence in season variable and unexpected demand. Therefore a new model of Decision Support System (DSS) that having analytical capability in stock management accurately and efficient is made by Analytic Hierarchy Process (AHP) that based on five influence factor, they are season, profit, price, unexpected demand and volume.The Decision Support System (DSS) produce a software that expected can help to determine priority of the kind of good that must be supplied in next year depend on the volume and time. It is useful to make easier decision that related to stock problem, therefore stock condition at stands of Laris department store always in controlled and the transaction process is going along smoothly.